Enjoying art: an evolutionary perspective on the esthetic experience from emotion elicitors - Serrao, Fabrizio; Chirico, Alice; Gabbiadini, Alessandro; Gallace, Alberto; Gaggioli, Andrea (Frontiers in Psychology, 2024)
The ubiquity of human art prompted evolutionary psychologists to explore its origins as a potential adaptation to the environment. Here we focus on emotionally charged art and posit that affective affordances embedded into some artworks play a pivotal role in explaining why these artworks are enjoyed from an evolutionary perspective. Such features, recurring in various art forms, are interpreted as cues to the emotional state of others, enabling art consumers to engage in empathetic experiences and vicarious emotions. We explore the adaptive value of deriving pleasure from vicarious emotions, while also addressing the seemingly counterintuitive enjoyment of artworks that evoke negative emotions. We discuss the appreciation of vicarious emotions irrespective of their valence and maintain this appreciation to hold adaptive significance for three key reasons. Firstly, it aids art consumers in refining their interpretational schemes of internal states, potentially enhancing emotional regulation skills. Secondly, it contributes to a deeper understanding of the emotions of others, thereby fostering emotional intelligence and empathy. Lastly, the enjoyment of affectively charged artworks reinforces social cohesion by harmonizing the emotions of group members.This perspective provides a comprehensive framework for understanding the evolutionary underpinnings of the human capacity for art appreciation and emotional engagement.